Protocol for the China PEACE (Patient-centered Evaluative Assessment of Cardiac Events) retrospective study of coronary catheterisation and percutaneous coronary intervention - Li, Jing (BMJ Publishing Group, 2014)
INTRODUCTION: During the past decade, the volume of percutaneous coronary intervention (PCI) in China has risen by more than 20-fold. Yet little is known about patterns of care and outcomes across hospitals, regions and time during this period of rising cardiovascular disease and dynamic change in the Chinese healthcare system. METHODS AND ANALYSIS: Using the China PEACE (Patient-centered Evaluative Assessment of Cardiac Events) research network, the Retrospective Study of Coronary Catheterisation and Percutaneous Coronary Intervention (China PEACE-Retrospective CathPCI Study) will examine a nationally representative sample of 11 900 patients who underwent coronary catheterisation or PCI at 55 Chinese hospitals during 2001, 2006 and 2011. We selected patients and study sites using a two-stage cluster sampling design with simple random sampling stratified within economical-geographical strata. A central coordinating centre will monitor data quality at the stages of case ascertainment, medical record abstraction and data management. We will examine patient characteristics, diagnostic testing patterns, procedural treatments and in-hospital outcomes, including death, complications of treatment and costs of hospitalisation. We will additionally characterise variation in treatments and outcomes by patient characteristics, hospital, region and study year. ETHICS AND DISSEMINATION: The China PEACE collaboration is designed to translate research into improved care for patients. The study protocol was approved by the central ethics committee at the China National Center for Cardiovascular Diseases (NCCD) and collaborating hospitals. Findings will be shared with participating hospitals, policymakers and the academic community to promote quality monitoring, quality improvement and the efficient allocation and use of coronary catheterisation and PCI in China. REGISTRATION DETAILS: http://www.clinicaltrials.gov (NCT01624896).